Distributed machine learning for IoT - Kadzhaia, Volodymyr; Raudys, Aistis; Raudys, Aistis (Vilnius University Open Series, 2022)
In the modern world, big data is used in machine learning, which is quite difficult to process on a single computer, so various methods for parallel processing of such data are being developed. But what about microcontrollers? In a cloud system, microcontrollers are often found, thanks to which they make pacification of various devices, and sometimes you have to work with big data. In microcontrollers, the memory is quite small and the processor is not as productive as on modern supercomputers. Therefore, many scientists propose various methods for parallel processing of big data for embedded systems, one of such methods is proposed by the author of this article.